A Concept called "scenema" a case study on the significance of Scenema Concept Inc. to the contemporary Filipino Film industry through a "behind-the-scenes" production for the movie "Solitaire" - Sia, Alevil B.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
For over a century now, Filipinos have been entertained, distracted, enriched, and affected in all possible ways by those flickering images on the silver screen. Movies have become an integral part of the Filipinos' lives. And yet, the Filipino film industry is in deep trouble. Local cinema is drowning in a sea of Hollywood films, and local producers are trying out one gimmick after another to attract moviegoers. What the industry needs is a more enlightened breed of producers who are willing to take risks rather than stick to the rules. This is a case study of newly put up production outfit called Scenema Concept Incorporated (SCI). SCI was established early early January of 1999 and spearheaded by Mr. LEO L. VILLALON, President and Chief Executive Officer of SEMICON (the nation's largest telecommunications distributor). It was conceptualized as a film production outfit with a difference. With this in mind, SCI's launching movie for the year 2000 is entitled "Solitaire." The researcher used the creation of a 'behind-the-scenes' production for "Solitaire," as a means to study SCI and its significance to the contemporary the Filipino film industry. To gain a picture of how the local industry is doing at present, the researcher interviewed some faculty members of the Film Department of UP College of Mass Communication. Newspaper articles and Internet articles supplemented the data gathered from the interviews. For the production output, the researcher used participant observation and shared in the production of "Solitaire" from October to December of 1999 as the creator of the 'behind-the-scenes' production. Using a video camera, the filming of "Solitaire" was documented. The producer, selected cast and some members of the crew were also interviewed. The researcher was not able to participate in the conceptualization of the film, since she began with SCI when they were already shooting their first scene. After the eight shooting day, the production was stopped due to several problems, and as a consequence, the researcher was not able to finish the study of the entire production. However, the researcher gathered enough data to conclude that SCI indeed strives to pursue its vision, which is to be "A Filipino motion picture company that aims to help uplift the movie industry into the global marketplace by redefining and shaping local style to bring them up to the international standard without losing our identity as a people and as a nation." The film "Solitaire" aspires to appeal to the educated Filipino taste when it comes to appreciating movies. In the spirit of bringing together world-class film technology and style with Filipino creativity and ingenuity, SCI commits itself to producing quality films with excellent production value. It strives to do so by choosing its projects carefully and investing in film equipment. SCI believes in "quality, not quantity." The researcher believes that in the light of a "troubled" local film industry, SCI is indeed a film production outfit that strives to be different.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Film producers -- Philippines